Comparative study on the liquid chromatographic enantioseparation of cyclic β-amino acids and the related cyclic β-aminohydroxamic acids on Cinchona alkaloid-based zwitterionic chiral stationary phases - Bajtai, Attila; Fekete, Beáta; Palkó, Márta; Fülöp, Ferenc; Lindner, Wolfgang; Kohout, Michal; Ilisz, István; Péter, Antal (Journal of separation science, 2018)
The enantiomeric pairs of cis and trans stereoisomers of cyclic β-aminohydroxamic acids and their related cis and trans cyclic β-amino acids containing two chiral centers were directly separated on four structurally related chiral stationary phases derived from quinine and quinidine modified with (R,R)- and (S,S)-aminocyclohexanesulfonic acids. Applying these zwitterionic ion-exchangers as chiral selectors, the effects of the composition of the bulk solvent, the acid and base additives, the structures of the analytes, and temperature on the enantioresolution were investigated. To study the effects of temperature and obtain thermodynamic parameters, experiments were carried out at constant mobile phase compositions in the temperature range 5-50°C. The differences in the changes in standard enthalpy Δ(ΔH°), entropy Δ(ΔS°), and free energy Δ(ΔG°) were calculated from the linear van't Hoff plots derived from the ln α versus 1/T curves in the studied temperature range. Results thus obtained indicated enthalpy-driven separations in all cases. The sequence of elution of the enantiomers was determined and found to be reversed when ZWIX(-)™ was changed to ZWIX(+)™ or ZWIX(-A) to ZWIX(+A).
Keywords: Thermodynamics; kyseliny hydroxamové; Stereoisomerism; enantioseparation; molekulární konformace; high-performance liquid chromatography; chininové alkaloidy; Amino Acids; Cinchona Alkaloids; beta-aminohydroxamic acids; termodynamika; aminokyseliny; Chromatography, Liquid; amino acids; chromatografie kapalinová; stereoizomerie; Hydroxamic Acids; Molecular Conformation